2013
DOI: 10.1038/srep01218
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic mechanism of protein cryopreservation in an aqueous solution with trehalose

Abstract: In order to investigate the cryoprotective mechanism of trehalose on proteins, we use molecular dynamics computer simulations to study the microscopic dynamics of water upon cooling in an aqueous solution of lysozyme and trehalose. We find that the presence of trehalose causes global retardation of the dynamics of water. Comparing aqueous solutions of lysozyme with/without trehalose, we observe that the dynamics of water in the hydration layers close to the protein is dramatically slower when trehalose is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(130 citation statements)
references
References 62 publications
8
121
0
Order By: Relevance
“…This possibly leads to its superior cryo-and lyoprotective properties [130]. MD simulations have been also performed in ternary LSZsugar-water systems at various sugar concentration [131][132][133][134]. More recently, a simulation of a solid state system composed by several LSZ proteins embedded in a low water glassy trehalose matrix has shown the presence of a more tight molecular packing of the proteins, which impairs the formation of large voids present in the dry LSZ glass without sugar [46].…”
Section: Atomistic Levelmentioning
confidence: 99%
“…This possibly leads to its superior cryo-and lyoprotective properties [130]. MD simulations have been also performed in ternary LSZsugar-water systems at various sugar concentration [131][132][133][134]. More recently, a simulation of a solid state system composed by several LSZ proteins embedded in a low water glassy trehalose matrix has shown the presence of a more tight molecular packing of the proteins, which impairs the formation of large voids present in the dry LSZ glass without sugar [46].…”
Section: Atomistic Levelmentioning
confidence: 99%
“…The p = 1 bar isobar has been simulated on the 300 K-200 K temperature range. Further computational details can be found in [73,74]. Hydration water has been defined by the following criterio: each water molecules lying at a distance minor than or equal to 6 Å from any protein atoms.…”
Section: Methodsmentioning
confidence: 99%
“…At a given temperature the long temporal evolution of the SISF, differently from the free-water confined in MCM-41 pore, can not be reliably described by one relaxational process, but two different structural processes are needed to reproduce the long time behavior of such curves [73]. Consequently two structural relaxation times can be extracted from the SISFs.…”
Section: Protein Hydration Watermentioning
confidence: 99%
See 1 more Smart Citation
“…The stabilization of the protein native structure was believed to be enhanced by the reduced electrostatic solvation properties of the water layer towards the protein in the presence of trehalose (Lins et al, 2004). Corradini et al (2013) found that trehalose entraps water at the protein interface by forming a transient structure described as a cage. They observed that the dynamics of water in the layers close to the protein is significantly slower when trehalose is present in aqueous solutions of lysozyme and concluded that this slow water keeps the protein hydrated and inhibits crystallization.…”
Section: Mechanisms Of Bioprotectionmentioning
confidence: 99%